Improving mental health literacy using web- or app-based interventions: A scoping review - Lidan Tian; Eliza Laiyi Wong; Dong Dong; Annie Wailing Cheung; Sherry Kit-wa Chan; Yuan Cao; Phoenix K.H. Mok; Lingming Zhou; Richard Huan Xu (Digital Health, 2024)
Background Given the rapid advancement in technology, the Internet has grown to play a significant role in the field of healthcare. Individuals can now access a profusion of easily available materials for self-management of their health. The purpose of this review is to describe Web/App-based interventions that are primarily or secondarily designed to improve mental health literacy (MHL) and to investigate the effectiveness of online interventions for improving mental health. Materials and Method A scoping review was conducted by searching five databases: PsycINFO, EMBASE, PubMed, CINAHL, and Web of Science. The search was limited to peer-reviewed journals published in English between 2000 and 2022. Studies focusing on enhancements of MHL or its constituent components were included. Results Twenty-four studies met the inclusion criteria. The interventions primarily targeted patients or individuals exhibiting symptoms of mental disorders, with a higher representation of female participants. All the interventions yielded positive outcomes. The included studies were categorized according to three themes: knowledge, attitude, and self-care skills. Although numerous studies have focused on knowledge improvement, research on interventions targeting self-care skills is scarce. Furthermore, existing literature on knowledge enhancement is limited in terms of the coverage of risk factors. Conclusion This review indicates gaps in web/app interventions including limited evidence on risk factors, inconsistent help-seeking awareness, and inadequate self-care skills training. Further research is critically needed to address these deficiencies and promote comprehensive MHL.